Improving the capacity of the Head of the sub civil service in regional apparatus organisation of the government in Malaka district - Oliva Bria Seran; M. N. B. C. Neolaka; Frans Gana (Journal of Governance and Accountability Studies, 2021)
Purpose: The purpose of this study was to examine the human resource capacity of the Head of Personnel Subdivision in the Organization of the Scope of the Malaka Regency Government, to find out supporting factors and constraints of the Human Resources Capacity its function and to find out the efforts taken by the Organization of the Regional Government of the Malaka Regency in increasing the capacity of Human Resources Head of Personnel Sub Division. Research methodology: The research method used in research was qualitative research methods with the type of case studies. Results: This study’s results are that human resource capacity is inadequate due to the low educational qualifications held by the Head of Personnel Sub-division within the scope of the Malaka district government. Limitation: This study’s limitation is that this research only focuses on the phenomena in the Malaka Regency so that the results of similar research can produce different findings if carried out on other research objects. Contribution: This research’s contribution is that it can provide scientific information for students of public administration programs and can be a scientific reference in the formulation and development of civil service innovations within the local government of Malaka Regency. Keywords: Capacity, Regional apparatus organization